BELAJAR BERDASAR REGULASI DIRI: DITINJAU DARI JENIS PENDIDIKAN - Junaidi Junaidi (Tarbiyatuna Kajian Pendidikan Islam, 2020)
This study aims to determine whether there are differences in learning based on students' self regulation MI Miftahul Ulum who follow character education and SDN 1 Bangsring characters that follow the conventional education with the control of emotional intelligence. This study involve 100 subjects in fifth grade elementary school, eachs were 50 students who followed the character education and 50 students who followed the conventional education. This study is use the analysis of covariance. This study showed that: there are differences in learning based on self-regulation among students who follow the character education with students who follow a conventional education. This is evidenced by the acquisition of the F = 8.531 (p <0.05). the effective character education to enhance self-learning ability based regulation.